Feasibility of Winter Oyster- Milky Mushroom Cropping Sequence for Year-Round Production under Assam Condition - Kataky, Madhusmita; Kalita, D. N.; Neog, M.; Sarma, R. K. (International Journal of Environment, Agriculture and Biotechnology, 2024)
The study was carried out during kharif and rabi season of 2018-19, 2019-20 and 2020-21 at 20 numbers of farmers field having low technology mushroom house at different locations of Assam. Existing farmers practice ie. growing of winter Oyster Mushroom alone from October to February under which farmers can grow two crops per year , was taken as control for comparision of farmer’s income with tested practice that is Winter Mushroom followed by Summer Mushroom Cropping sequence . The specific objective of the study was to demonstrate the double cropping of Mushroom Farming viz. Winter Oyster Mushroom followed by Milky Mushroom. The study showed that under the tested double cropping sequence, five crops comprising three crops for Winter Mushroom (September to March)and two crops for Summer Milky Mushroom (April to August)can be grown per year. It was observed that in a 15 feet X 18 feet low technology mushroom house, 400 bags per batch can be accommodate. The winter Oyster and Milky Mushroom cropping system produced the average winter Oyster yield of 2931.6kg per year from 3 batches (400 bags/batch)and an average Milky Mushroom yield of 1240kg from 2batches (five batches in a year)compared to an average yield of 1320kg per year from 2 batches in a year (400 bags per batch) obtained at farmers practice. The percentage yield increase of Winter Oyster – Milky Mushroom cropping sequence (average of three years) over farmers practice was recorded as 216%. The economic analysis showed that growing Milky Mushroom during summer season enhance additional income to the growers who usually grow winter oyster mushroom as single crop for 5 months. Hence growing Winter Oyster Mushroom – Milky Mushroom crop sequence for the year round is a potential income generating enterprise which can be adopted by farmers and unemployment youth of Assam.